Making sense of the specifications. IN HDTV Buying Guide. - Poor, Alfred
Before you purchase an LCD plasma or plasma flat-panel HDTV, read our comprehensive buying advice to learn what features to consider.
Keywords: Video Electronics Standards Association; High definition television; Three-dimensional display systems; Video Graphics Array (VGA).; Separate video (S-Video).; LCD HDTV; High-Definition Multimedia Interface (HDMI).